2015
DOI: 10.1186/s12938-015-0007-7
|View full text |Cite
|
Sign up to set email alerts
|

Forced oscillations and respiratory system modeling in adults with cystic fibrosis

Abstract: BackgroundThe Forced Oscillation Technique (FOT) has the potential to increase our knowledge about the biomechanical changes that occur in Cystic Fibrosis (CF). Thus, the aims of this study were to investigate changes in the resistive and reactive properties of the respiratory systems of adults with CF.MethodsThe study was conducted in a group of 27 adults with CF over 18 years old and a control group of 23 healthy individuals, both of which were assessed by the FOT, plethysmography and spirometry. An equivale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
39
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 56 publications
13
39
1
Order By: Relevance
“…Because mean reactance reflects the inhomogeneity of the respiratory system, we believe that the irregular distribution of preferential involvement in the upper lobes and changes in the small airways may explain, at least in part, the decline of mean reactance in adults with CF. 7,44 In addition, we observed higher impedance module at 4 Hz values in adults with CF than in controls. The impedance module at 4 Hz is related to the total mechanical load of the respiratory system, describing the effect resulting from respiratory system resistance, compliance, and inertia.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Because mean reactance reflects the inhomogeneity of the respiratory system, we believe that the irregular distribution of preferential involvement in the upper lobes and changes in the small airways may explain, at least in part, the decline of mean reactance in adults with CF. 7,44 In addition, we observed higher impedance module at 4 Hz values in adults with CF than in controls. The impedance module at 4 Hz is related to the total mechanical load of the respiratory system, describing the effect resulting from respiratory system resistance, compliance, and inertia.…”
Section: Discussionmentioning
confidence: 56%
“…These regions exhibited a higher density than the parenchyma with normal aeration, which suggests the presence of areas of consolidation, collapse, and fibrosis in CF. [7][8][9][10][11][12][13][14][15][16][17][18][19] Considering clinical practice, lungvolume quantification using multidetector CT may con-tribute to the early identification of lung disease. In fact, we have found that the presence of poorly aerated regions on inspiratory lung-volume quantification using multidetector CT has good accuracy for diagnosing pulmonary disease in CF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reactive properties were interpreted using parameters widely used in the literature: the dynamic compliance ( C dyn ), which includes the compliance of the lung and bronchial walls, the chest wall/abdominal compartment, the thoracic gas compression and the upper airways (associated with the soft tissues of the mouth, cheeks and pharynx) . This parameter was estimated using Xrs at 4 Hz [ C dyn = −1/(2 πfX 4)]; the resonance frequency (Fr) is defined as the frequency at which Xrs equals zero; the mean reactance (Xm) is a property usually related to the respiratory system's non‐homogeneity . The total mechanical load of the respiratory system was estimated using the absolute value of respiratory impedance at 4 Hz (Z4Hz) and included the resistive and elastic effects .…”
Section: Methodsmentioning
confidence: 99%
“…These abnormalities have been reported in young patients with mild CF (6) and in clinically stable individuals without detectable infection (714). Using the single frequency forced oscillation technique, decreases in reactance (Xrs) and increases in resistance (Rrs) of the respiratory system in CF patients has been reported, although the magnitude of these differences was not consistent across studies (7, 1517), likely due to variability of clinical status in these cohorts. Taken together, these findings indicate that a phenotype of altered pulmonary function is present early in the course of CF, independent of documented infections, or onset of pulmonary symptoms.…”
Section: Introductionmentioning
confidence: 99%